The Relationship Between CYP19 Gene Polymorphism and Pregnancy Hormone in Awassi Ewes: Hubungan Antara Polimorfisme Gen CYP19 dan Hormon Kehamilan pada Domba Awassi - AL-Jubouri, Razzaq Nasser Abed; Kareem, Yousif Hamad; ALkhuzai, Fouad Lazim Jasim (Universitas Muhammadiyah Sidoarjo, 2024)
Leuconostoc mesenteriodes is an important probiotic bacteria with impact characteristics and benefits for human health. Last year, probiotic bacteria were used as an alternative to traditional antibiotics in treat of different diseases especially in the broad distribution of MDR bacteria. L. mesenteriodes isolate was purchased from (Al-Amin Center for Research and Biotechnology Najaf, Iraq) and re-diagnosis using MRS media in anaerobic condition then diagnosis by vitek 2 system. The antibacterial activity of L. mesenteriodes was assessed using the agar well diffusion method against MDR pathogenic bacteria isolated from different clinical cases. The L. mesenteriodes crude was obtained by centrifuging the bacterial isolates. Five different concentrations of probiotic bacteria crude were tested against MDR pathogenic bacteria revealing the antibacterial activity of L. mesenteriodes crude concentrations (stock, 90%, 75%, 50% and 25% ) against MDR Staphylococcus aureus (22, 20, 20, 17, 14 mm), MDR Micrococcu. leuts (24, 23, 18, 16, 11 mm), MDR Proteus. mirabillis (22, 22, 18, 17, 14 mm), MDR Escherichia. coli (22, 20, 18, 12, 11 mm) and MDR Klebsiella pneumoniae were (20, 18, 14, 12, 11mm) an respectively. L. mesenteriodes probiotics improve antibacterial activity especially when used against multi-drug resistant bacteria Highlights: Study CYP19 exon 8 polymorphisms and pregnancy hormones in Awasi sheep. Genotype distribution: TT (20%), TC (30%), CC (50%); TC highest (P<0.05). TC genotype linked to higher pregnancy hormone levels than TT, CC.. Keywords: Exon8. CYP19 Gene . Awassi ewes . pregnancy hormone.